Hubungan antara kebimbangan komunikasi dengan komitmen terhadap organisasi : satu kajian ke atas anggota polis pangkat rendah di Jabatan Pengurusan, Ibu Pejabat Polis Kontinjen Johor - Hussain, Hasani Hashim (2013)
The main purpose of this study conducted is to identify the communication apprehension and organizational commitment among low rank police personnel at Management Department Police Headquarters of Johor Contingent. The objective of this study are to identified the level of communication apprehension and organizational commitment, to determine the relationship between communication apprehension and organization commitment and to examine the difference of communication apprehension based on the demographics factors. PRCA-24 and Organization Commitment Questionnaire (Mowday, Porter and Steer, 1982) were used in collecting the data. The total of respondents involved in this study were 163. Besides that, the data have been analyzed by using Statistical Package for Social Science (SPSS) software, version 20.0 and the quantitative methodology was introduced in this study. The likert scale was being used to measure the level of the communication apprehension and organizational commitment. The findings of this study showed that the level of communication apprehension was at moderate level with min 2.87, while organizational commitment at the high level with min 3.82. The result reveal that there is negative significant relationship between communication apprehension and organization commitment among respondent (r=-.515, p<0.000). The result also show that there were no difference based on demography factor such as gender, age, marital status and education level except working experience.